Correlation Of Blast Design And Ground Vibration During Blasting At Imerys (M) Sdn Bhd. - Mohd. Saad, Nuraizul Azren (Universiti Sains Malaysia, 2022)
As a result of growing mining and construction activity in areas close to human populations, ground vibration has evolved into a significant environmental problem due to the fact that it has the potential to irritate people and cause damage to structures. Study was conducted at Imerys (M) Sdn Bhd, Ipoh, Perak to study the ground vibration. The objective of this research is to develop a method to analyse the correlation between blast design and ground vibration which are to establish the relationship between peak particle velocity (PPV) and the scaled distance by using regression analysis and to determine the site constant law that can adopt in PPV in USBM equation to predict ground vibration by quarry. Blast monitoring, data collection and regression analysis was performed to accomplish objective of this study. Regression analysis was performed to determine the site constant and the prediction on the regression value. The R-square value obained came close to reaching 1.0, which indicates that all variations in the dependent variable are totally explained by the independent variables. The value of K and B from a confidence level of 95 percent was used to predict the value of PPV by plugging in 70 kilogrammes of charge per delay and 300 metres of distance into the equation; the result is 3.74 millimetres per second. From the regression analysis, the distance and the weight charge (scaled distance) both have substantial influences on the intensity of vibration.